2010
DOI: 10.1016/j.rse.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The potential of the MERIS Terrestrial Chlorophyll Index for carbon flux estimation

Abstract: In this study we evaluated the potential of the Medium Resolution Imaging Spectrometer (MERIS) Terrestrial Chlorophyll Index (MTCI) for monitoring gross primary productivity (GPP) across fifteen eddy covariance towers encompassing a wide variation in North American vegetation composition. The acrosssite relationship between MTCI and tower GPP was stronger than that between either the MODIS GPP or EVI and tower GPP, suggesting that data from the MERIS can be used as a valid alternative to MODIS for estimating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 38 publications
6
43
0
Order By: Relevance
“…2), as well as low and high frequency variations of PAR in . Chl-related VI closely follow seasonal changes in Chl content (Almond et al, 2010;Gitelson et al, 2005;Harris & Dash, 2010;Wu et al, 2009). In the green-up stage, VI alone relate closely to GPP, while in reproductive and senescence stages, as PAR in declines, discrepancies between VI and GPP increased Sakamoto et al, 2011).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…2), as well as low and high frequency variations of PAR in . Chl-related VI closely follow seasonal changes in Chl content (Almond et al, 2010;Gitelson et al, 2005;Harris & Dash, 2010;Wu et al, 2009). In the green-up stage, VI alone relate closely to GPP, while in reproductive and senescence stages, as PAR in declines, discrepancies between VI and GPP increased Sakamoto et al, 2011).…”
Section: Methodsmentioning
confidence: 86%
“…The VI-PAR in -based model (Eq. 3), with MTCI derived from MERIS images, was capable of estimating GPP accurately across a variety of land cover and vegetation types (Almond et al, 2010;Harris & Dash, 2010). Wu et al (2010aWu et al ( , 2011 showed that maize GPP could be estimated with high accuracy using the VI-PAR inbased model with MODIS data.…”
Section: Methodsmentioning
confidence: 97%
“…The statistical-empirical method is typically based on a regression function that links measured biochemical or biophysical parameters to spectral measurements [7,8], such as spectral reflectance [9,10], spectral indices [11][12][13][14], red-edge features [15][16][17][18], absorption features [19][20][21][22], and band combinations made using the wavelet transformation or principal transformation [23][24][25][26]. However, the leaf spectrum depends on a complex interaction between internal and external factors that may vary significantly from one species to another, and it is hard to build a universal relationship between a single vegetation variable and a spectral signature [27].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the assumption that chlorophyll is related to the presence of photosynthetic biomass, which is essential for primary production and thus conceptually related to GPP , recent studies (Gitelson et al, 2008;Harris and Dash, 2010) suggest that GPP can be estimated through direct correlation with chlorophyll-related indexes. Successful results have been obtained in agricultural crops (Gitelson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%